João Albasini e as luzes de Nwandzengele: jornalismo e política em Moçambique, 1908-1922 - Albasini, João dos Santos (Alcance, 2014)
Keywords: Activistes Mozambique Biographies; Albasini, João; Albasini, João dos Santos, 1876-1922; Biographies; Journalists; Journalists Mozambique Biography; Mozambique; Political activists; Political activists Mozambique Biography; Press and politics; Press and politics Mozambique; biographies (form); journalism; journalists; political action; political conditions

Photar Moçambique - Alexandre, Paulo; Couto, Mia (Porto Editora, 2014)

Dentro da pedra, ou, A metamorfose do silêncio: poesia - Arijuane, Japone (Tsilana, 2014)
Keywords: Poetry; Poésie; poetry

Dentro da pedra ou a metamorfose do silêncio - Arijuane, Japone; Cabrita, António; Gonçalves, Delmar Maia (Tsilana, 2014)

Os filhos da Costa do Sol: a nova geração - Arouca, Manuel (Colecção Gradiva, 2014)
Keywords: Portugiesisch; Roman

Vila Algarve - Azevedo, Francisco Duarte; Fonseca, Fernanda (Planeta Manuscrito, 2014)

O fundo pardo das coisas: poesia - Bucuane, Juvenal; Cuna, Aurélio (Poesia, 2014)
Keywords: Anthologie; Lyrik; Mozambican poetry (Portuguese); Moçambique; Poetry; Portugiesisch; Poésie; poetry

A esposa do quadro - Buque, Adelino (Adelino Buque, 2014)
Keywords: Historical fiction; Mozambique History 20th century Fiction; Novellas

Contos e gravuras no sul de Moçambique - Cabrita, António; Nhaca, Jorge; Gandolfo, Gianfranco (Kapicua, 2014)

Onde está Têi-Têi? galeria de retratos de Moçambique - Can, Azira (Papiro, 2014)

Discurso e poder nos romances de João Paulo Borges Coelho - Can, Nazir (Alcance Editores, 2014)
Keywords: Coelho, João Paulo Borges; Criticism and interpretation; Mozambican literature (Portuguese)

Poalha de MussaM'Biki: pensamentos, narrativas e poesia - Canotilho, Ribeiro; Viegas, Jorge (CEMD - Círculo de Escritores Moçambicanos na Diáspora, 2014)

52 semanas - César, Miguel (Prosa, 2014)

Predio 333 - Clássica (FUNDAC, 2014)
Keywords: Fiction; Novels; Romans; novels

A súplica de D. Pedro - Constâncio, Natália (Viagens na ficção, 2014)

A menina sem palavra - Couto, Mia (Boa Companhia, 2014)
Keywords: Contos moçambicanos

Antes de nascer o mundo - Couto, Mia (Companhia das Letras, 2014)
Keywords: Ficção moçambicana

Cada homem é uma raça: contos - Couto, Mia (Caminho, 2014)

Contos do nascer da Terra - Couto, Mia (Companhia das Letras, 2014)
Keywords: Contos moçambicanos; Fiction; Short stories, Mozambican (Portuguese)

Contos do nascer da terra - Couto, Mia (Caminho, 2014)

Contos do nascer da Terra: contos - Couto, Mia (Caminho, 2014)

E se Obama fosse africano? e outras interinvenções: ensaios - Couto, Mia (Companhia das Letras, 2014)
Keywords: Ensaios moçambicanos

Estórias abensonhadas: contos - Couto, Mia (Companhia das Letras, 2014)
Keywords: Contos moçambicanos

Jesusalém: romance - Couto, Mia (Caminho, 2014)

Na berma de nenhuma estrada e outros contos - Couto, Mia (Caminho, 2014)

Na berma de nenhuma estrada e outros contos - Couto, Mia (Caminho, 2014)

O fio das missangas: contos - Couto, Mia (Companhia das Letras, 2014)
Keywords: Contos moçambicanos

O fio das missangas: contos - Couto, Mia (Caminho, 2014)

O outro pé da sereia - Couto, Mia (Companhia das Letras, 2014)
Keywords: Ficção moçambicana

O último voo do flamingo - Couto, Mia (Outra margens, 2014)

Pensageiro frequente - Couto, Mia (Crónicas, 2014)

Raiz de orvalho e outros poemas: poesia - Couto, Mia (Caminho, 2014)

Terra sonâmbula - Couto, Mia (Companhia das Letras, 2014)
Keywords: Ficção moçambicana

Terra sonâmbula - Couto, Mia (Companhia das Letras, 2014)
Keywords: Ficção moçambicana

Terra sonâmbula: romance - Couto, Mia (Ondas do índico, 2014)
Keywords: 1900-1999; Famines; Famines Mozambique Histoire 20e siècle Romans, nouvelles, etc; Famines Mozambique History 20th century Fiction; Fiction; History; Mozambican fiction (Portuguese); Mozambique; Mozambique Fiction; Mozambique Histoire 1975-1994 Romans, nouvelles, etc; Mozambique History Independence and Civil War, 1975-1994 Fiction; Violence; Violence Mozambique Histoire 20e siècle Romans, nouvelles, etc; Violence Mozambique History 20th century Fiction

Um rio chamado tempo, uma casa chamada terra - Couto, Mia (Companhia das Letras, 2014)
Keywords: Ficção moçambicana

Um rio chamado tempo, uma casa chamada terra - Couto, Mia (Bis, 2014)

Um rio chamado tempo, uma casa chamada terra: romance - Couto, Mia (Bis, 2014)

Vagas e lumes: poesia - Couto, Mia (Caminho, 2014)
Keywords: 18.37 Portuguese literature; 2000-2099; History; Lyrik; Mozambican poetry (Portuguese); Mozambique; Mozambique Conditions sociales Poésie; Mozambique Histoire Poésie; Mozambique History Poetry; Mozambique Poetry; Mozambique Social conditions Poetry; Poetry; Portugiesisch; Poésie; Social conditions; poetry

Venenos de Deus, remédios do Diabo - Couto, Mia (BIS, 2014)

Venenos de Deus, remédios do Diabo - Couto, Mia (Leya, 2014)

Venenos de Deus, remédios do diabo: as incuráveis vidas de Vila Cacimba - Couto, Mia (Companhia das Letras, 2014)
Keywords: Ficção moçambicana

Vinte e zinco: romance - Couto, Mia (Caminho, 2014)
Keywords: 1975-1994; Fiction; History; Littérature portugaise; Mozambique; Mozambique Histoire 1975-1994 Romans, nouvelles, etc; Mozambique History Independence and Civil War, 1975-1994 Fiction; Portuguese literature

Vozes anoitecidas - Couto, Mia (Caminho, 2014)

Vozes anoitecidas: contos - Couto, Mia (Companhia das Letras, 2014)
Keywords: Contos moçambicanos

Mar me quer - Couto, Mia; Pereira, João Nasi (Caminho, 2014)

Mar me quer - Couto, Mia; Pereira, João Nasi (Caminho, 2014)

O beijo da palavrinha - Couto, Mia; Wojciechowska, Danuta (Caminho, 2014)

O beijo da palavrinha - Couto, Mia; Wojciechowska, Danuta (Caminho, 2014)

O beijo da palavrinha - Couto, Mia; Wojciechowska, Danuta (Caminho, 2014)

O beijo da palavrinha - Couto, Mia; Wojciechowska, Danuta (Caminho, 2014)

O gato e o escuro - Couto, Mia; Wojciechowska, Danuta (Caminho, 2014)

O gato e o escuro - Couto, Mia; Wojciechowska, Danuta (Caminho, 2014)

O menino no sapatinho - Couto, Mia; Wojciechowska, Danuta (Caminho, 2014)

Chigubo - Craveirinha, José (Autores ultramarinos, 2014)

Karingana ua Karingana - Craveirinha, José (Oitocentos anos de literaturas em português, 2014)

Ao encontro da vida ou da morte - D'África, Deusa (Poesia, 2014)

Equidade no reino celestial - D'África, Deusa (Romance, 2014)

Colectânea Gaza e Niassa: vozes do Hiterland - D'África, Deusa; Miambo, Elísio; Amures, Mucuruza Lily do (Poesia, 2014)

Nhatsi: elos e laços - Davambe (Scortecci, 2014)
Keywords: Ficção moçambicana

A voz das minhas entranhas - Deusa d'Africa (Poesia, 2014)
Keywords: Poetry

Godido: e outros contos - Dias, João (África nova, 2014)

Godigo e outros contos - Dias, João (Karinga, 2014)

O mar de Maputo: lwandle ra kaMaputsu : the Maputo sea - Díaz, Rafo (Conto infantil, 2014)
Keywords: Indian Ocean Maputo Bay; Maputo Bay (Mozambique) Juvenile fiction Pictorial works; Maputo, Baie de (Mozambique) Romans, nouvelles, etc. pour la jeunesse Ouvrages illustrés; Mozambican fiction (Portuguese); Mozambique; Mozambique Juvenile fiction Pictorial works

O casamento misterioso de Mwidja - Dunduro, Alexandre; Mondlane, Orlando José (Contos e histórias de Moçambique, 2014)
Keywords: Artizanat Mozambic; Literatură portugheză (Mozambic) Povestiri

As Armadilhas da Floresta - Faife, Hélder; Manhiça, Mauro (Contos e histórias de Moçambique, 2014)
Keywords: Literatură portugheză (Mozambic) Povestiri

Moçambique marcou-nos para a vida: grupo de mulheres internacionalistas, 1980-1984 retratos e depoimentos - Fuchs, Elisa (JV Editores, 2014)

Antologia dos silêncios que cantamos - Gonçalves, Delmar Maia (Poesia moçambicana, 2014)

Mares de olhares em mestiçagens de poesia: pensamento, provérbios, aforismos e poemas - Gonçalves, Delmar Maia (CEMD - Círculo de Escritores Moçambicanos na Diáspora, 2014)

Revista Cultural Milandros da Diáspora, 2014 - Gonçalves, Delmar Maia (CEMD - Círculo de Escritores Moçambicanos na Diáspora, 2014)

Moçambique: para a mãe se lembrar como foi - Gonzaga, Manuela (Bertrand Editora, 2014)
Keywords: Biography; Gonzaga, Manuela; Journalists; Mozambique; Portugal; Social life and customs

O cheiro da chuva: memórias de Moçambique - Hewlett, John (s.n., 2014)
This is a true African tale of persistence and tenacity. The story of a farmer and pilot raised in colonial Kenya who went on to play an active role in Mozambican politics whilst leading Lonrho's foreign investment in that country. This unique memoir describes life during Mozambique's transition from communism to democracy, from poverty to an investor's choice. It has been a life creating farms, gold mining and operating hotels through war and peace. Then supporting peasant farmers and developing the conservation of a private tropical island. It is proof that nothing is impossible and Africa offers opportunity to those who persist. It is a personal record of the changes in modern Africa and Mozambique in particular an investor's destination. It should also be an enjoyable read
Keywords: Biography; Businessmen; Hewlett, John; Lonrho (Firm); Mozambique

Nós matámos o cão-tinhoso! - Honwana, Luís Bernardo (Prosa, 2014)
Keywords: Africa, Portuguese-speaking; Africa, Portuguese-speaking Social life and customs Fiction; Afrique lusophone Mœurs et coutumes Romans, nouvelles, etc; Criticism, interpretation, etc; Fiction; History and criticism; Honwana, Luís Bernardo; Honwana, Luís Bernardo, 1942-; Honwana, Luís Bernardo, 1942- History and criticism; Manners and customs; Mozambican fiction (Portuguese); Mozambique; Mozambique Fiction; Portuguese-speaking Africa; Short stories, Mozambican (Portuguese); Social life and customs

Nós matámos o cão-tinhoso - Honwana, Luís Bernardo (Bolso Cotovia, 2014)
Keywords: 1900-1999; Fiction; History; Mozambican fiction (Portuguese); Mozambique; Mozambique Histoire 20e siècle Romans, nouvelles, etc; Mozambique History 20th century Fiction; Roman mozambicain (portugais)

Efémera liberdade - Ismael, Amilca; Barreiros, Adriana; Seixas, João Manuel Peres de (A métrica da alma, 2014)

Efémera liberdade - Ismael, Amilca; Barreiros, Adriana; Seixas, João Manuel Peres de (A Métrica da Alma, 2014)

Mitombwe - João, Benjamim Pedro (Colecção Nthepo, 2014)

Kok Nam: preto no branco - Kok, Nam (Serie Kulungwana, 2014)
Keywords: Kok, Nam

A marrabenta: sua evolução e estilização, 1950 - 2002 - Laranjeira, Rui (Minerva Print, 2014)

cada um em Mim poesia - Lineu, Nelson (Revista Literatas, 2014)

Cada um em mim - Lineu, Nelson; Angius, Fernanda (Literatas, 2014)

Feitiços - Machado, Graça Pereira (Edita-me, 2014)

Antologia inédita: outras vozes de Moçambique - Manjate, Lucílio; Okapi, Sangare (Poesia, 2014)
Keywords: Mozambican poetry (Portuguese); Mozambique Poetry Literary collections

Almas periféricas: poesia - Mapindza (Livaningo cartão d'arte, 2014)
Keywords: Artists' books; Artists' books Mozambique Specimens; Cartonera books; Cartonera books Mozambique Specimens; Corrugated board bindings (Binding); Livres d'artistes Mozambique Spécimens; Mozambican poetry (Portuguese); Mozambique; Petites maisons d'édition Mozambique Spécimens; Poésie mozambicaine (portugaise); Small presses; Small presses Mozambique Specimens; Specimens

Jasmins & chambre - Matiangola (s.n., 2014)
Keywords: Essais; Essay; Essays; essays

Sonhos, caminhos & lutas: antologia poetica - Barga, Alex (MOLIJU, 2014)
Keywords: 2000-2099; Mozambican poetry (Portuguese); Mozambican poetry (Portuguese) 21st century; Poésie mozambicaine (portugaise) 21e siècle

Íntimos rascunhos: poesia - Moiane, Américo António (Livaningo cartão d'arte, 2014)
Keywords: Artists' books; Artists' books Mozambique Specimens; Cartonera books; Cartonera books Mozambique Specimens; Corrugated board bindings (Binding); Livres d'artistes Mozambique Spécimens; Mozambican poetry (Portuguese); Mozambique; Petites maisons d'édition Mozambique Spécimens; Poésie mozambicaine (portugaise); Small presses; Small presses Mozambique Specimens; Specimens

Os elefantes pisam... mas não matam a savana - Mosca, João (Alcance, 2014)
Keywords: Mozambique

O intérprete de Deus: romance - Mudender, Élio Martins (s.n., 2014)
Keywords: Novellas; novellas

Caderno de memórias - Muianga, Aldino (Alcance, 2014)
Keywords: Authors Mozambique 20th-21st century Memoirs; Authors, MozambicanvBiography; Mozambique; Muianga, Aldino; Social life and customs

Caderno de memorias: volume I - Muianga, Aldino (Colecção Prosa, 2014)
Keywords: Authors, Mozambican; Authors, Mozambican Biography; Biographies; Manners and customs; Mozambique; Mozambique Social life and customs; Muianga, Aldino, 1950-; prose (form); Écrivains mozambicains Biographies

Vontades de partir e outros desejos poesia - Mukurruza, L. (FUNDAC, 2014)

Vontades de partir & outros desejos - Mukurruza, Lino (s.n., 2014)

A vingança de Jesus Cristo - Neves, Osvaldo das (Livaningo, 2014)

Contos e gravuras do sul de Mo̧cambique - Nhaca, Jorge; Cabrita, António (Kapicua, 2014)
Keywords: Folk tales; Mozambique; Nhaca, Jorge; Wood-engraving

Omitir não é mentir - Osvaldo, Carlos (Prosa, 2014)
Keywords: Conduct of life; Conduct of life Fiction; Engagement rings; Engagement rings Fiction; Fiction; Man-woman relationships; Man-woman relationships Fiction; Mensonge Romans, nouvelles, etc; Morale pratique Romans, nouvelles, etc; Mozambican fiction (Portuguese); Novels; Relations entre hommes et femmes Romans, nouvelles, etc; Romans; Truthfulness and falsehood; Truthfulness and falsehood Fiction; novels

O gala-gala cantor - Patraquim, Luís Carlos; Ralha, Ivone (Conto infantil, 2014)

Kikiriki: uma monografia do maestro Filipe Machiana - Pereira, Ciro (Série Kulungwana, 2014)
Keywords: Biographies; Choral conductors; Choral conductors Mozambique Biography; Composers; Composers Mozambique Biography; Compositeurs Mozambique Biographies; Machiana, Filipe, 1934-; Mozambique

A última história de amor: três mulheres unidas pelo sangue e por África romance - Queirós, Conceição; Agualusa, José Eduardo; Alvim, João Carlos (Romance, 2014)

Tchaneze, a Donzela de Sena - Roque, Carlos Paradona Rufino; . (Fonte de Palavra, 2014)

Singularidades III - Rosário, Lourenço Joaquim da Costa (Teses, 2014)
Keywords: 1900-1999; 20th century; Africa; Africa, Portuguese-speaking; Africa, Portuguese-speaking Civilization Foreign influences; African literature (Portuguese); African literature (Portuguese) 20th century History and criticism; Afrique lusophone Civilisation Influence étrangère; Civilization; Civilization Foreign influences; Criticism, interpretation, etc; Education; Education Mozambique; Foreign influences; History and criticism; Mozambique; Mozambique Conditions sociales; Mozambique Social conditions; Portugais (Langue) Régionalismes Afrique; Portuguese language; Portuguese language Provincialisms; Portuguese language Provincialisms Africa; Portuguese-speaking Africa; Provincialisms; Social conditions; articles (form); education; folk tales (form); literature

O Puto: autópsia dos ventos da liberdade - Saavedra, Ricardo de (Quetzal, 2014)
About Manuel Vicente da CruzGaspar, better known as Puto, counter-revolutionary activist
Keywords: 1900-2002; Africa; Afrique du Sud Histoire 1961-1994; Angola; Angola Histoire 1975-2002 (Guerre civile); Angola History Civil War, 1975-2002; Biographies; Cruz Gaspar, Manuel Vicente da, 1954-; Decolonization; Decolonization Africa, Portuguese-speaking; Décolonisation Afrique lusophone; Fiction; Guerrillas; Guerrillas Mozambique Biography; History; Mozambique; Mozambique Histoire 1964-1975 (Révolution); Mozambique Histoire 1975-1994; Mozambique History Independence and Civil War, 1975-1994; Mozambique History Revolution, 1964-1975; Portugal Colonies Africa History 20th century; Portugal Colonies Histoire 20e siècle; Portuguese colonies; Portuguese-speaking Africa; Revolutionaries; Revolutionaries Mozambique Biography; Révolutionnaires Mozambique Biographies; South Africa; South Africa History 1961-1994

Antologias de poesia da Casa dos Estudantes do Império, 1951-1963 (UCCLA, 2014)
Keywords: African poetry (Portuguese); Mozambican poetry (Portuguese); Poésie africaine (portugaise); Poésie mozambicaine (portugaise)

Feteni, o aldeão de Lipangu - Sambu, Malahleki (Alcance, 2014)
Keywords: Mozambique; novels (form)

O pacto das elites e sua representação no romance em Angola e Moçambique - Saraiva, Sueli da Silva (AULP - Associação das Universidades de Língua Portuguesa, 2014)

A criação da memória - Secca, Mário Forjaz (Prazeres poéticos, 2014)

Afeto & poesia: ensaios e entrevistas : Angola e Moçambique - Secco, Carmen Lúcia Tindó (Oficina Raquel : CNPq, 2014)
Keywords: 1900-1999; Affect (Psychology) in literature; Angolan poetry (Portuguese); Angolan poetry (Portuguese) 20th century History and criticism; Authors, Angolan; Authors, Angolan 20th century Interviews; Authors, Mozambican; Authors, Mozambican 20th century Interviews; Criticism, interpretation, etc; Interviews; Mozambican poetry (Portuguese); Mozambican poetry (Portuguese) 20th century History and criticism; Poésie angolaise (portugaise) 20e siècle Histoire et critique; Poésie mozambicaine (portugaise) 20e siècle Histoire et critique; Écrivains angolais 20e siècle Entretiens; Écrivains mozambicains 20e siècle Entretiens

A cor dos bichos - Silva, Calane da; Oliveira, Paula; Pereira, Ciro (Edição do autor, 2014)

Ricardo Rangel: insubmisso e generoso - Silva, Calane da; Thompson, Drew; Honwana, Luís Bernardo; Lopes, Mota; Saúte, Nelson; Hayes, Patricia (Série Kulungwana, 2014)
Keywords: Mozambique; Photographes de presse Mozambique; Photojournalists; Photojournalists Mozambique; Rangel, Ricardo

Olhar de uma africana - Tavares, Margarida (Poesia Fã Clube, 2014)

Apocalipse dos predadores - Timóteo, Adelino (Viagens na ficção, 2014)

Tempos a ferro e fogo: irmãos e inimigos - Torcato, Maria de Lourdes (Missanga, 2014)
Keywords: Anti-apartheid movements; Influence; Influence (Literary, artistic, etc.); Mandela, Nelson; Political aspects; Reconciliation; South Africa

O velho e o mato: romance - Veiga, Sérgio; Sousa, Silvina de (Os livros RTP, 2014)
Keywords: Fiction; Portugiesisch; Roman

Da poesia? ou de como se justifica um ponto de interrogação - Viegas, Jorge; Novo, Vera Novo; Gonçalves, Delmar Maia (CEMD - Circulo de Escritores Moçambicanos na Diáspora, 2014)

Passei por Maputo - Waty, Teodoro Andrade (W. Editora, 2014)
Keywords: Cities and towns; Maputo; Maputo (Mozambique); Mozambique; Mozambique Maputo; Politics and government

Bom dia, dia - White, Eduardo; Almeida, José (Versus, 2014)